Simplifying
13 = 2f + 5
Reorder the terms:
13 = 5 + 2f
Solving
13 = 5 + 2f
Solving for variable 'f'.
Move all terms containing f to the left, all other terms to the right.
Add '-2f' to each side of the equation.
13 + -2f = 5 + 2f + -2f
Combine like terms: 2f + -2f = 0
13 + -2f = 5 + 0
13 + -2f = 5
Add '-13' to each side of the equation.
13 + -13 + -2f = 5 + -13
Combine like terms: 13 + -13 = 0
0 + -2f = 5 + -13
-2f = 5 + -13
Combine like terms: 5 + -13 = -8
-2f = -8
Divide each side by '-2'.
f = 4
Simplifying
f = 4
SO, f = 4
13 = 2 × 4 + 5
Hope I helped:P